Comparison of Anthropometric and Physical Fitness Variables Based on Gender and Position in Elite Field Hockey Players - Jane Kim; Hee-Jung Park; Do-Youn Kim; Su-Jin Kim; Dong-Ho Park (운동과학)
PURPOSE The aim of this study was to derive anthropometric and fitness characteristics required by sex and position in Korean elite field hockey athletes. METHODS This study included 14 male (29.8±3.6 years) and 14 female (27.2±3.5 years) elite field hockey players. They were examined for anthropometric (weight, height, %body fat, etc.) and physical fitness variables (push-up, sit-up, side-steps, etc.), including isometric strength (handgrip and back & leg strength), anaerobic capacity (Wingate 30s test), and trunk isokinetic peak torque (30°/s and 120°/s). RESULTS Male players outperformed female players on most physical fitness variables. Specifically, female athletes had significantly lower isometric muscle strength (26–37%, p<.001) and anaerobic capacity (36%, p<.001) than male athletes, but these differences were less pronounced in measures of muscle power variables (12–23%, p<.001) and cardiorespiratory endurance (14%, p<.001). Forwards (FW) excelled in push-ups compared to defenders (DF; p<.05), and midfielders (MF) had higher mean and peak powers in the Wingate tests compared to FW and DF (p<.05). Finally, the correlation between anthropometric and physical fitness variables appears to differ depending on sex. CONCLUSIONS Male athletes performed better than female athletes on most physical fitness measures, although differences were observed depending on their motor ability. MF showed higher anaerobic power than FW and DF. In addition, the correlation between anthropometric and physical fitness variables appears to differ depending on sex. Therefore, the findings of the present study emphasize the need for sex-specific and positional demands in training programs to optimize performance.